2004
DOI: 10.1094/mpmi.2004.17.8.837
|View full text |Cite
|
Sign up to set email alerts
|

The Necrotic Pathotype of theCucumber mosaic virus(CMV) Ns Strain Is Solely Determined by Amino Acid 461 of the 1a Protein

Abstract: The unique Ns isolate of Cucumber mosaic virus (CMV) induces necrotic lesions on several Nicotiana spp. in contrast to other strains that cause systemic mosaic on these plants. By using biologically active RNA transcripts from cDNAs of Ns-CMV and a reference subgroup I strain Rs-CMV, we confined the genetic determinant solely responsible for necrosis induction to amino acid 461 of the la protein translated from genomic RNA1. An Arg to Cys change at this position (R461C) rendered Rs-CMV necrotic, whereas the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Two studies reported that CMV RNA1, CMV 1a protein residue 461, was directly implicated as a virulence determinant [13], [41]. Although RNA1 was not directly implicated as an avirulence determinant, other reports have shown that RNA1 is involved in determining the severity of symptoms [42], [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that CMV RNA1, CMV 1a protein residue 461, was directly implicated as a virulence determinant [13], [41]. Although RNA1 was not directly implicated as an avirulence determinant, other reports have shown that RNA1 is involved in determining the severity of symptoms [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…RNA1 was determined to be an avirulence determinant of the hypersensitive response in tobacco [13], [14], local and systemic movement in squash [15], and replication of satellite RNA in squash [16], [17]. Avirulence determinants involving RNA2 were identified by induction of the hypersensitive response in cowpea [18], [19] and hypervirulence and systemic movement in tobacco [11], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Description of the Rs-CMV and the infectious transcripts (pRs1, pRs2, pRs3) has been published previously [43]. A STOP codon was introduced into pRs2 into the 2a protein ORF just preceding the start codon of the 2b protein by PCR directed mutagenesis (pRs2-2a777) using the following oligonucleotides: 5′-CGTT GAGCTC CAT ATT ACTTTCGCTGTTTGTTGG-3′ (reverse), 5′-TATG GAGCTC AACGTAGGTGCAATGACAAACG-3′ (forward).…”
Section: Methodsmentioning
confidence: 99%
“…Xanthi. Divéki et al . (2004) showed that an amino acid at position 461 in the 1a protein is the determinant for cell death, i.e.…”
Section: Virulence Determinantsmentioning
confidence: 99%